Piezo-Particulate Composites Manufacturing, Properties, Applications - Khanbareh, Hamideh; Topolov, Vitaly Yu; Bowen, Christopher R. (Springer Series in Materials Science, 2019)
This book provides an overview of the current state of the art in novel piezo-composites based on ferroelectrics. Covering aspects ranging from theoretical materials simulation and manufacturing and characterization methods, to the application and performance of these materials, it focuses on the optimization of the material parameters. Presenting the latest findings on modern composites and highlighting the applications of piezoelectric materials for sensors, transducers and hydro-acoustics, the book addresses an important gap in the physics of active dielectrics and materials science and describes new trends in the research on ferroelectric composites.